2004
DOI: 10.1097/01.asn.0000113316.52371.2e
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Neoangiogenesis in Human Kidney Transplants Is Associated with Immunologically Active Lymphocytic Infiltrates

Abstract: Abstract. Renal transplant rejection is caused by a lymphocyterich inflammatory infiltrate that attacks cortical tubules and endothelial cells. Immunosuppressive therapy reduces the number of infiltrating cells; however, their exit routes are not known. Here a Ͼ50-fold increase of lymphatic vessel density over normal kidneys in grafts with nodular mononuclear infiltrates is demonstrated by immunohistochemistry on human renal transplant biopsie susing antibodies to the lymphatic endothelial marker protein podop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
388
5
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 426 publications
(418 citation statements)
references
References 26 publications
21
388
5
3
Order By: Relevance
“…As previously described by Kerjaschki et al (2004) in transplanted kidneys, we found nodular cellular infiltrates within the regions of higher LV count. To further characterize the infiltrating cell populations, IHC stainings for B lymphocytes, that is, CD20 for B cells and CD27 for plasma cells, were performed.…”
Section: Higher Occurrence Of B Lymphocytes In MM Kidneyssupporting
confidence: 88%
See 3 more Smart Citations
“…As previously described by Kerjaschki et al (2004) in transplanted kidneys, we found nodular cellular infiltrates within the regions of higher LV count. To further characterize the infiltrating cell populations, IHC stainings for B lymphocytes, that is, CD20 for B cells and CD27 for plasma cells, were performed.…”
Section: Higher Occurrence Of B Lymphocytes In MM Kidneyssupporting
confidence: 88%
“…Most data about renal lymphangiogenesis have so far been obtained in kidney transplant recipients with either acute graft rejection or chronic allograft nephropathy (Kerjaschki et al, 2004;Adair et al, 2007;Stuht et al, 2007). In both cases, the number of lymph vessels was much higher when compared with native nephrectomy tissue; however, there was no significant difference in LV density between different Banff rejection grades and chronic allograft nephropathy (Stuht et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult lymphangiogenesis occurs during inflammation and wound healing [1,10], but is also strongly associated with chronic inflammation, autoimmunity, and allograft rejection [11][12][13][14][15][16] as well as with tumor invasion and metastasis when initiated both around the tumor and in the draining LN [17][18][19][20][21]. These are all associated with different immunological outcomes: from Th1 and Th2 inflammatory responses to immune escape and tolerance.…”
Section: Introductionmentioning
confidence: 99%